The Recent Electoral Reforms in Federally Administered Tribal Areas (FATA): An Appraisal - Altaf Ullah; Syed Umar Hayat (Journal of Political Studies, 2017)
This research study explores electoral reforms in Federally Administered Tribal Areas (FATA) of Pakistan introduced by the last PPP-P government in August 2011. The initiative of the government to formally allow political activities in FATA by extending the Political Parties Act 2002 to these areas is a mega political move to accommodate tribal population in the national mainstream. The formal commencement of political activities in FATA was a long- cherished demand of the tribal people for which they were waiting for a long period. The previous electoral processes and voting behaviour in FATA benefited a limited number of tribal elites. Those elites such as Maliks and lungi holders were the main political beneficiaries who monopolized politics prioritizing their selfish interests. However, the recent electoral reforms are basically a paradigm shift in the political system of those areas and that is the main focus of the present study. It also critically evaluates how the political parties incorporated the FATA related issues in their respective political manifestos and electoral slogans during the 2013 general elections which was the first party-based electoral move in FATA after the political reforms in those areas. The study contains a comprehensive account of the pre-polls political activities, terrorism and its impact on the overall electoral process and outcome of the 2013 general elections in FATA. This discourse is, however, aimed at an analysis based on perceptions about the social and political paradigm shifts in FATA especially and approaches of the federal government of Pakistan directed towards the concerned situation in the tribal localities of Pakistan generally.